2018
DOI: 10.1021/acsnano.7b08816
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Fourier’s Law of Heat Transport in Quantum Electron Systems

Abstract: The microscopic origins of Fourier's venerable law of thermal transport in quantum electron systems has remained somewhat of a mystery, given that previous derivations were forced to invoke intrinsic scattering rates far exceeding those occurring in real systems. We propose an alternative hypothesis, namely, that Fourier's law emerges naturally if many quantum states participate in the transport of heat across the system. We test this hypothesis systematically in a graphene flake junction and show that the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Instead, the linear profile of T * i is associated with the substantial broadening of the spectral peaks in A(ω). 5 This means that the thermal transport process involves electronic states in a wide range of energies. The phases of these states are averaged out when T * i are measured, which leads to a classical-like behavior.…”
Section: Local Temperatures Of Multi-impurity Systems and The Effect Of Quantum Resonancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the linear profile of T * i is associated with the substantial broadening of the spectral peaks in A(ω). 5 This means that the thermal transport process involves electronic states in a wide range of energies. The phases of these states are averaged out when T * i are measured, which leads to a classical-like behavior.…”
Section: Local Temperatures Of Multi-impurity Systems and The Effect Of Quantum Resonancesmentioning
confidence: 99%
“…Inui et al 5 have reported strong oscillations of temperature distribution in a graphene flake weakly coupled to the electrodes under a thermal bias due to quantum interference. But in their study the local temperatures T * ,ZCC i still remain constant on a relatively small scale in the weak-coupling regime, similar to the curve of T * ,ZCC i in Fig.…”
Section: Local Temperatures Of Multi-impurity Systems and The Effect Of Quantum Resonancesmentioning
confidence: 99%
“…To address this issue, Inui et al have studied the Fourier's law in graphene flakes subjected to a thermal bias [433]. Figure 38 shows the calculated local temperature distribution for two different graphene-electrode contact geometries [433]. In the type I contact only the left and right edges of the flake couple to the electrodes, while for type II contact two electrodes cover three edges of the flake, leading to a stronger coupling.…”
Section: Recovering Fourier's Law At the Nanoscalementioning
confidence: 99%
“…The local temperature distributions for type I contact exhibit strong oscillations that depend on µ 0 , while for type II contact, the distributions resemble the classical distribution. Reprinted with permission from [433]. Copyright 2018 American Chemical Society.…”
Section: Recovering Fourier's Law At the Nanoscalementioning
confidence: 99%
See 1 more Smart Citation